Welheidsbediening deur AGS-pastore in 'n stedelike konteks: 'n verkennende kwalitatiewe ondersoek - Lovell, L.; Lotter, G. A. (Faculty of Theology, University of the Free State, 2010)
A total change of culture is happening in the world, and the church should take cognisance of it because people’s religious experience is not detached from their cultural context. In the light of the changing contemporary culture and new challenges for the ministry, the research question was posed: Why is a wellness ministry by AFM pastors in an urban context necessary and what should it entail in guiding people towards wellness? The objective of the research on which this article is reporting, was to research a wellness ministry by AFM pastors in an urban context. In this article, it is demonstrated how empirical research can be used to produce important results in understanding the necessity of a wellness ministry by AFM pastors in an urban context. In a qualitative investigation with eight pastors, which included a pilot study, valid results were obtained.
Keywords: Wellness; Ministry; Churches; Holistic; Dimensions